2021
DOI: 10.1007/s41669-021-00289-0
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Ireland’s Cost-Effectiveness Threshold: New State-Industry Drug Pricing Deal Should Adequately Reflect Opportunity Costs

Abstract: Ireland’s cost-effectiveness threshold is currently €45,000 per quality-adjusted life-year (QALY). It has previously been determined by periodic agreements between the State and a pharma industry lobby body. A new deal is due in July 2021 and it is therefore timely to re-examine Ireland’s threshold, how it is set and transparency around adherence to it. Previous research has noted a series of problems with the threshold, including that it is likely too high relative to the opportunity cost of unmet need within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The NCPE’s HTA concluded that the ICER for dupilumab in adult patients with moderate-to-severe, refractory AD exceeded €66,000 per QALY. This is well above the threshold of €45,000/QALY that has been used within the decision making processes in Ireland [ 8 , 25 ]. The predicted gross budget impact estimate was €38.3 million over 5 years, with the licence extension granted to the adolescent population expected to increase the budget impact substantially.…”
Section: Discussionmentioning
confidence: 98%
“…The NCPE’s HTA concluded that the ICER for dupilumab in adult patients with moderate-to-severe, refractory AD exceeded €66,000 per QALY. This is well above the threshold of €45,000/QALY that has been used within the decision making processes in Ireland [ 8 , 25 ]. The predicted gross budget impact estimate was €38.3 million over 5 years, with the licence extension granted to the adolescent population expected to increase the budget impact substantially.…”
Section: Discussionmentioning
confidence: 98%
“…The cost-effectiveness of the vaccine was assessed in terms of discounted life years lost, QALYs, and incremental cost-effectiveness ratios (ICERs) against a cost-effectiveness threshold of EUR 45,000/QALY [ 36 , 37 ]. QALYs were discounted at an annual rate of 3%.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, those with PHI can bypass aspects of the public hospital system by accessing private care within both public and private hospitals. If the introduction of universal health care in Ireland includes the removal of private practice from public hospitals (thereby reducing the ability of those with PHI to access private services), those with PHI may prefer a continuation of the status quo rather than supporting reforms that will likely require an increase in taxation (O'Mahony, 2021) and potentially impact on their ability to access health care in a timely manner. Recently, objections were raised by members of the public (and medical professionals) about the removal of private maternity care from public hospitals with some arguing that this would reduce choice for patients given the lack of private maternity hospitals (Malone, 2023).…”
Section: Reform Proposals But Limited Implementation: Why?mentioning
confidence: 99%